2011
DOI: 10.1590/s0103-50532011000800019
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular complexes formed by the association of poly(ethyleneimine) (PEI), sodium cholate (NaC) and sodium dodecyl sulfate (SDS)

Abstract: A formação de complexos supramoleculares em solução aquosa pela associação do polieletrólito poli(etilenoimina) (PEI) com misturas do biossurfactante colato de sódio (NaC) e o surfactante aniônico dodecil sulfato de sódio (SDS) foi aqui investigado usando as técnicas de condutivimetria, tensiometria, fluorimetria, espalhamento de raios X a baixos ângulos (SAXS) e medidas de pH. Os resultados de fluorimetria, condutivimetria e medidas de pH levaram à conclusão de que os monômeros de NaC e SDS ligam-se primeiram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 50 publications
3
8
0
1
Order By: Relevance
“…The protonation of amine in water can in situ generate hydroxide ions, which acts as a base catalyst for the isomerization reaction. However, the addition of a neutral salt can greatly influence the protonation of amine in water. Specifically, the salt can promote the protonation of amine through changing the activity coefficients of all ionic species in the solution, and the protonation constant of amine is a function of the ionic strength. , Upon the addition of salt, the protonated amine can form a complex with the anion of salt through electrostatic interaction, and the stability of the complex increases with increasing the protonation. The salt ions can influence differently the water dissociation and hence shift the acid–base equilibrium and increase the pH value of the amine aqueous solution.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The protonation of amine in water can in situ generate hydroxide ions, which acts as a base catalyst for the isomerization reaction. However, the addition of a neutral salt can greatly influence the protonation of amine in water. Specifically, the salt can promote the protonation of amine through changing the activity coefficients of all ionic species in the solution, and the protonation constant of amine is a function of the ionic strength. , Upon the addition of salt, the protonated amine can form a complex with the anion of salt through electrostatic interaction, and the stability of the complex increases with increasing the protonation. The salt ions can influence differently the water dissociation and hence shift the acid–base equilibrium and increase the pH value of the amine aqueous solution.…”
Section: Resultssupporting
confidence: 53%
“…The salt ions can influence differently the water dissociation and hence shift the acid–base equilibrium and increase the pH value of the amine aqueous solution. Previous research has shown that the addition of salts such as sodium chloride and lithium chloride created conformational changes and increased the pH value of a PEI aqueous solution from 7.0 to around 9.0. , The PEIs in this study were positively charged weak polyelectrolytes due to the protonation of the primary, secondary, and tertiary amines, as indicated by the observed positive zeta potentials shown in Figure S7. The positively charged PEIs can specifically bind with anions of salts through electrostatic interactions.…”
Section: Resultsmentioning
confidence: 62%
“…At this point, all of the active groups of the polymer are already occupied by individual particles or micelles from the surfactant and any excess forms free micelles, unrelated to the polymer chain ( Fig. 6 ) [ 26 27 ]. All of these processes affect the kinetics of the precipitation reaction of tin dioxide nanoparticles and cause a change in their size.…”
Section: Resultsmentioning
confidence: 99%
“…29,31,36 No entanto, esta técnica pode interferir na obtenção de valores de cmc e cac, pela possível perturbação da estrutura micelar, decorrente da baixa solubilidade do pireno, formando agregados pré-micelares. …”
Section: Fluorescênciaunclassified